Bioinspired low-magnetic Zr alloy with high strength and ductility. (1st July 2021) - Zhou, Weiwei; Sun, Xiaohao; Tsutsumi, Yusuke; Nomura, Naoyuki; Hanawa, Takao
Abstract: Generally, high strength and high ductility are two mutually exclusive properties of engineering materials. Nacre exhibits high strength and toughness owing to the presence of intelligent brick-and-mortar architectures. The present study demonstrates the design of a bioinspired nacre-like Zr-1Mo alloy via an appropriate thermomechanical treatment. The α-Zr phases and the elongated β-Zr nanoparticles in the alloy functioned as the hard bricks and soft mortar, respectively. Consequently, the nacre-like Zr-1Mo alloy possesses a high potential for biomaterial applications owing to its unique combination of high tensile strength (~812–968 MPa), high ductility (~10.3–12.6%), and low magnetic susceptibility (~1.2–1.4 × 10 −6 cm 3 g −1 ). This work provides new insights into the fabrication of bioinspired metallic materials with exceptionally high strength and ductility. Graphical abstract: Image, graphical abstract